PENGARUH PARTISIPASI ANGGOTA DAN LINGKUNGAN USAHA TERHADAP KEBERHASILAN KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) KAPAS KECAMATAN SUSUKAN KABUPATEN BANJARNEGARA - Setiaji, Khasan (Semarang State University, 2009)
There are some factors which is retard and encourage to get the success in cooperation, likebusiness environment and build the members participation. The aim of this research is to know theinfluence and how much the influence of members participation and business environment towards thesuccess of Ã¢â¬ÅKPRI KapasÃ¢â¬Â Banjarnegara. The participation of members and business environmentbecome a free variable, meanwhile the success of Ã¢â¬ÅKPRI KapasÃ¢â¬Â become a bounded variable. Based onthe result the percentage descriptive analysis, we got 69% for the members participation and 74,07% forbusiness environment and we conclude that is was be good category, meanwhile we got 67,44% for thesuccess of Ã¢â¬ÅKPRI KapasÃ¢â¬Â and we conclude good enough category. The percentage of influencemembers participation and business environment toward the successful of Ã¢â¬ÅKPRI KapasÃ¢â¬Â was 58,5%,meanwhile the rest was 41,5% influenced by the other factors. To be more success this cooperationneed relationship whit the other business optimally and need education and training for the members.Keywords: members participation, business environment, success of KPRI Kapas